EFEKTIVITAS PENYELESAIAN SENGKETA TANAH MELALUI HUKUM ADAT DI DESA HILIMBARUZO KECAMATAN MAZO KABUPATEN NIAS SELATAN - Laia, Aferianus (JURNAL PANAH KEADILAN, 2025)
One may say that issues involving property or land disputes are common in Indonesia because there is a lack of legal clarity about land that is owned by people or organizations. In Hilimbaruzo Village, Mazo District, a land dispute including crop destruction and redrawing of land ownership borders was settled in accordance with customary law. The purpose of this study is to determine how well Hilimbaruzo Village, Mazo District, South Nias Regency, uses customary law to settle property disputes. The study methodology is sociological legal research, which looks at relevant legal provisions in light of societal realities as they exist. Primary, secondary, and tertiary data were used in the data gathering process. acquired from secondary Qualitative data analysis is the method employed. Analyzing qualitative data is done concurrently with the process of gathering data. The resolution of land disputes using customary punishments differs between land disputes that happened in 2014 and land conflicts that happened in 2018, according to the research findings and discussion in this study. Based on these findings, the researcher suggests that the best way to resolve land disputes in the village of Hilimbaruzo, Mazo District, South Nias Regency is through customary law, which should be upheld and continued. This is because using customary law to resolve land disputes is the most effective way to resolve criminal acts and is advantageous to both parties.